Synchronization of Sanctions Against Corruption by Village Heads - Marvika Aries Triana; Kukuh Budi Mulya (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2022)
ABSTRACT There is a dis-synchronization between Law Number 6 of 2014 concerning Villages and Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption, related to the regulation of sanctions against corruption by the Village Head, which is contained in article 30 of the Village Law with articles 2 and Article 3 of the Law on the Eradication of Corruption Crimes results in uncertainty in the implementation of law enforcement. This research uses a normative juridical research method, using a statutory approach, a conceptual approach and a case approach.This research aims to interpret the provisions of Article 30 of the Village Law which is interpreted to be in dis-synchronization with the provisions of Article 2 and Article 3 of the Corruption Eradication Act and to find a legal solution for the dis-synchronization of two regulations regarding sanctions against Village Heads who commit corruption..The results show that the handling of cases regarding corruption in village funds carried out by the Village Head should be resolved using the Corruption Eradication Act, although according to the Village Law, it imposes administrative sanctions and legal solutions for the dis-synchronization of the two regulations regarding sanctions against the Village Head the one who commits corruption is to change the articles that have been dis-synchronized in part or all of the articles of the relevant laws and regulations, by the institutions/agencies authorized to form them.